Going Online: The Affordances of Online Counseling for Families Affected by Alcohol and Other Drug Issues. (December 2019) - Dilkes-Frayne, Ella; Savic, Michael; Carter, Adrian; Kokanović, Renata; Lubman, Dan I.
Online counseling can overcome barriers families face when accessing support services for issues such as a relative's alcohol or other drug use. However, little research has explored how online counseling platforms assist family members to improve their well-being and support their relative. We thematically analyzed 90 transcripts of online counseling sessions with family and friends of people who use alcohol, opioids, and amphetamines in Australia between 2015 and 2016. In our analysis, we drew on the concept of affordances to articulate how online platforms afford or constrain potentially therapeutic encounters with families. We found online counseling enabled families to make first contact, relieve distress, plan appropriate action, improve communication, regain direction, and connect with local services. Sessions were constrained by Internet access, web-chat communication, counselors' focus on referral, and limitations in addressing the wider concerns of families. The findings present opportunities for improving online services for families.